The rise of the Ottoman Empire : studies in the history of Turkey, thirteenth-fifteenth centuries - Wittek, Paul, 1894-1978.; Heywood, Colin; Lindner, Rudi Paul.; Welsh, Oliver (Milton Park, Abingdon ; New York : Routledge, 2012)
"Wittek's The Rise of the Ottoman Empire was first published by the Royal Asiatic Society in 1938, and has been out of print for more than a quarter of a century. The opportunity has been taken at the present reissue of Wittek's 1937 London lectures to bring together in one volume translations of his other studies on Ottoman history, dating mainly from his Brussels years. This book contains five closely interconnected writings by Wittek on Ottoman history during the century and a half from the founding of the state to the Fall of Constantinople. All but one of these pieces reproduces the texts of lectures or conference papers delivered by Wittek between 1936 and 1938. The journals in which they were originally published are for the most part inaccessible except in specialist libraries, it seems, in a period when Wittek's activities as an Ottoman historian are coming under increasing study within the Anglo-Saxon world of scholarship. An introduction sets Wittek's work in its historical and historiographical context for the benefit of those students not privileged to experience it firsthand, and the book is an interesting contribution to studies on Asian and Middle East history"--
pt. I. The rise of the Ottoman Empire -- pt. II. Precursors of The rise.
Originally published: London : Royal Asiatic Society, 1938.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Turkey -- History -- 1288-1453.; Electronic books